Analysis Of The Influence Of Work Discipline And Work Motivation On Employee Performance At PT Indomarco Adi Prima Tegal - Ikhwan, Khairul Ikhwan; Barros, Agapito Barros; Hartono, Budi Hartono (International Journal Business and Entrepreneurship, 2024)
Human resources are the prime mover of the course of an organization's activities, the success of an organization is determined by the existence of its human resources. So that human resources or employees in an organization become an important concern in the context of efforts to achieve organizational success. The purpose of this study was to determine the effect of work discipline on employee performance at PT Indomarco Adi Prima Tegal, to determine the effect of motivation on employee performance at PT Indomarco Adi Prima Tegal, to determine the effect of work discipline and motivation simultaneously on employee performance at PT Indomarco Adi Prima Tegal. The sample in this study was 45 respondents and used multiple linear regression analysis as an analytical tool. The results of this study are work discipline has no significant but positive effect on employee performance. Work motivation has a significant and positive effect on employee performance. Work discipline and work motivation together have a significant effect on employee performance